A Sociolinguistics Analysis of Address Terms in Sasak Language - Rajabul, Moh. Gufron (Department of Languages and Literature, Faculty of Cultural Sciences, UGM, 2023)
This research falls under the broad category of linguistics, i.e., sociolinguistics, which investigates the relationship between language and society. The objective of this research is to examine the sociolinguistic phenomenon known as